2017
DOI: 10.1002/eji.201646775
|View full text |Cite
|
Sign up to set email alerts
|

Card9 controls Dectin‐1‐induced T‐cell cytotoxicity and tumor growth in mice

Abstract: Activation of the C‐type lectin receptor Dectin‐1 by β‐glucans triggers multiple signals within DCs that result in activation of innate immunity. While these mechanisms can potently prime CD8+ cytotoxic T‐cell (CTL) responses without additional adjuvants, the Dectin‐1 effector pathways that control CTL induction remain unclear. Here we demonstrate that Dectin‐1‐induced CTL cross‐priming in mice does not require inflammasome activation but strictly depends on the adapter protein Card9 in vitro. In vivo, Dectin‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Interestingly, CARD9 as an inflammation-related gene also promote the proliferation and migration of tumor cells, induce cancer, and affect tumor severity and prognosis 81 .…”
Section: Importance Of Card9 In Non-infection-related Inflammationmentioning
confidence: 99%
“…Interestingly, CARD9 as an inflammation-related gene also promote the proliferation and migration of tumor cells, induce cancer, and affect tumor severity and prognosis 81 .…”
Section: Importance Of Card9 In Non-infection-related Inflammationmentioning
confidence: 99%
“…For example, administration of β glucans was shown to inhibit tumor growth in murine carcinoma models ( 13 15 ), in human melanoma, neuroblastoma, mastocytosis, and lymphoma xenograft models ( 16 , 17 ) and in ovarian ( 18 , 19 ), breast ( 20 ), lung ( 14 , 21 23 ), and gastric cancer ( 19 , 24 ). Mechanistically, β glucans were shown to convert immunosuppressive macrophages into an M1-like antitumoral phenotype ( 25 ), to promote NK ( 26 ) and CD8 + T cell cytotoxicity ( 27 ) as well as a decrease in myeloid-derived suppressor cells and regulatory T cells ( 13 , 28 ). Interestingly, Zhao et al recently reported that β glucans upregulate particularly the expression of TNFSF15 and OX40L in DCs in mice, thus promoting efficient Th9 priming and potent anti-melanoma response following vaccination ( 29 ).…”
Section: “(Dectin-1)” Familymentioning
confidence: 99%
“…Dectin-1 ligation on DCs was further shown to capacitate DCs for priming of cytotoxic CD8 + T cells (63). Dectin-1-activated cross-priming of cytotoxic CD8 + T cells by DCs depends on caspase recruitment domain family member 9 (Card9) but does not depend on the activation of inflammasomes (64). In humans, DECTIN-1 stimulates mast cells to produce leukotrienes (55), which have recently been shown to be involved in the activation of ILCs (65), thereby providing another line of cross-talk between myeloid cells and innate lymphocytes.…”
Section: Hemitam Receptorsmentioning
confidence: 99%